Managing inter-organizational collaborations : process views - Sydow, Jörg; Berends, Hans (Research in the sociology of organizations, 2019)
This volume contains two Open Access Chapters. Volume 64 of Research in the Sociology of Organizations takes stock of research on processes of inter-organizational collaboration and explores new topics that call for inquiry. It shows that inter-organizational collaboration is becoming more varied and fluid. Traditional strategic alliances and consortia are still around, but these are complemented with new forms of collaboration, often enabled by emerging digital technologies.The volume is organized in three parts. The first set of chapters focus on relational dynamics of inter-organizational collaboration. Process views of inter-organizational collaboration investigate the relational embeddedness of interactions, the development and change of relations, and how relationships are constituted as processual phenomena. The second part of this volume addresses organizational dynamics in collaboration processes. Organizations themselves are not stable in any collaboration: just as collaboration is fluid, also organizations continuously change, and intra-organizational dynamics are key to understand external collaboration. Third, this volume addresses new phenomena in the changing landscape of inter-organizational collaboration, thereby laying out directions for future inquiry.